A BIBLIOMETRIC ANALYSIS OF ISLAMIC REGTECH RESEARCH INDEXED BY DIMENSION.AI - Yaser Taufik Syamlan; Muhammad Syafii Antonio (Airlangga International Journal of Islamic Economics and Finance, 2023)
Currently the issuance of Paper on Islamic Regtech published by a journal equipped with title and abstract identifiers is registered in Dimension.ai from 2019 to 2023 explored in this bibliometric study. The focus of the investigation is on the keyword and author's pattern. The data was examined from the 15 Dimension research article (https://dimension.ai). 'Islamic Regtech' is a search keyword. On February 23, 2023, the search used to make a collection of study data was updated. The bibliometric map was found using a descriptive statistical approach and bibliometric analysis using a vos viewer. The quantity of paper on Islamic Regtech, as well as the growth of Islamic digital regulations, has increased dramatically in recent years. This topic is covered by a number of journals, one of the best is Ethical Concerns in Artificial Intelligence (AI): The Role of Regtech and Islamic Finance. Research, Disruption, and Islamic Financial Institution are the most commonly used terms. This study provides an overview of the most popular key words and writers in the publication with the topic of Islamic Regtech, with the hope that it can be useful information for academics who work in this field. Thus, this concept will potentially be further developed in the future.